Manajemen Persediaan Barang pada Outlate Amanda Brownies di Kota Pasuruan - Jadid, Muhammad Nurul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The results of this study aim to help analyze inventory management at the Amanda Brownies outlet branch in Pasuruan City. This research employed a qualitative method by conducting direct interviews with employees of the Amanda Brownies outlet branch to obtain data used in inventory calculations. Based on the interviews, the employees stated that inventory management had never been carried out before. Therefore, this study attempts to calculate ordering costs and identify items that should be prioritized using the ABC method to assist the owner in managing the inventory. The results show that the ABC method can help the Amanda Brownies outlet branch in Pasuruan City determine which items should be prioritized. The ABC method also helps the owner identify the optimal order quantity and frequency